Insectivorous Birds Dominate Across Land-Use Gradient Revealing Unexpected Ecological Resilience in Tropical Forest-Coffee Landscapes - pardede, lusiana; Iswandaru, Dian; Rahma Fitriana, Yulia; Darmawan, Arief; Kaskoyo, Hari; Wulandari, Christine; Safe'I, Rahmat; Herwanti, Susni; Novriyanti, Novriyanti; Gumay Febryano, Indra (Forestry Department, University of Muhammadiyah Makassar, 2025)
Vegetation is essential for birds to fulfil their life requirements. Monoculture coffee plantations, coffee-based agroforestry systems, and forests in HKm Wana Jaya provide potential habitats for various animal species, including birds. This research assessed bird diversity, richness, evenness, species dominance, feeding guilds, and conservation status across these three land cover types. The point count method was employed for data collection. Data were quantitatively analysed using the Shannon-Wiener diversity index, the Margalef richness index, the Pielou evenness index, and the Simpson dominance index. The study recorded 35 bird species from 19 families comprising 167 individuals. Species diversity values across all three land cover types fell within the moderate category, with forest exhibiting the highest value (2.988), followed by coffee agroforestry (2.648) and monoculture coffee (2.035). The highest species richness was found in the forest (5.429) and the lowest in monoculture coffee (2.970). The highest species evenness was recorded in coffee agroforestry (0.935) and the lowest in monoculture coffee (0.849), while species dominance values across all three land cover types were categorised as low (0.061-0.172). Insectivorous birds dominated feeding guilds across all habitat types, revealing unexpected ecological resilience. Of the species recorded, 29 are classified as Least Concern, two as Vulnerable, four as Near Threatened, while 10 species are protected under national legislation, and three species are listed in CITES Appendix II. The findings suggest that while forests maintain the highest biodiversity value, coffee agroforestry systems can provide crucial supplementary bird conservation habitats in modified landscapes.